2017
DOI: 10.1093/jee/tox083
|View full text |Cite
|
Sign up to set email alerts
|

Interspecific Competition Between Ceratitis capitata and Two Bactrocera Spp. (Diptera: Tephritidae) Evaluated via Adult Behavioral Interference Under Laboratory Conditions

Abstract: The Mediterranean fruit fly, Ceratitis capitata (Wiedemann), is considered one of the most invasive tephritid species. It has spread and established populations successfully throughout many of the tropical temperate regions, partially owing to the increase in global trading activity that facilitates diffusion of species. However, C. capitata has never been detected in China, even though some areas of the country have favorable climate and ample food resources. Historically, some researchers have hypothesized t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 26 publications
1
9
0
Order By: Relevance
“…Its host range includes more than 250 fruit and vegetable crops 3 ; therefore, the infestation by fruit fly imposes significant economic losses primarily due to direct fruit damage and the accrued cost for export limitations associated with quarantine and eradication measures 4 – 6 . Furthermore, B. dorsalis is highly competitive with other invasive and harmful tephritid fruit flies and quickly becomes the dominant tephritid species in a new area 7 , 8 . For instance, within a short time of introduction of B. dorsalis in Hawaii, the population of Ceratitis capitata , another major tephritid fruit fly pest of economic importance, declined severely, such that adult flies or infested fruits could rarely be found in coastal areas 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Its host range includes more than 250 fruit and vegetable crops 3 ; therefore, the infestation by fruit fly imposes significant economic losses primarily due to direct fruit damage and the accrued cost for export limitations associated with quarantine and eradication measures 4 – 6 . Furthermore, B. dorsalis is highly competitive with other invasive and harmful tephritid fruit flies and quickly becomes the dominant tephritid species in a new area 7 , 8 . For instance, within a short time of introduction of B. dorsalis in Hawaii, the population of Ceratitis capitata , another major tephritid fruit fly pest of economic importance, declined severely, such that adult flies or infested fruits could rarely be found in coastal areas 2 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, previous studies have shown that oviposition competition occurs between adult females. Liu et al (2017) showed that B. dorsalis species has a clear advantage when competing with C. capitata for egg-laying. Aggressive behaviour has been observed in some fruit fly species, including B. dorsalis.…”
Section: The Competitive Displacementmentioning
confidence: 99%
“…These species have been investigated because of their increasingly wide distributions and repeated invasions. The Bactrocera genus has a competitive advantage for oviposition over other fruit flies such as Ceratitis capitata which is one of the most devastating and invasive worldwide pests (Liu, Zhang, Hou, Ou-Yang, & Ma, 2017;Malacrida et al, 2007). The two Bactrocera species are similar in many biological attributes such as mating duration, oviposition preference, and offspring performance as well as sharing a common origin.…”
Section: Introductionmentioning
confidence: 99%
“…However, the geographical distribution of B. dorsalis is now much wider than that of B. correcta both in China and elsewhere in the invasive range, which B. dorsalis has invaded including Hawaii, Kenya, and Tahiti and gradually displaced pre-established Ceratitis species in recent years (Figure 1; Hu, Chen, & Li, 2014;Liu et al, 2014;Liu, Jin, & Ye, 2013;Lux, Copeland, White, Manrakhan, & Billah, 2003;Reitz & Trumble, 2002). Thus far, there are no records of B. dorsalis being displaced by other tephritid fly species (Liu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%